Find dy /dx if x=ln (y-e ^-y)?

Asked on by nurli

1 Answer | Add Yours

Top Answer

sciencesolve's profile pic

sciencesolve | Teacher | (Level 3) Educator Emeritus

Posted on

You need to write y in terms of x, such that:

`x = ln (y - e ^(-y)) => y - e ^(-y) = e^x`

You need to differentiate both sides with respect to x, such that:

`(dy)/(dx) + e^(-y)*(dy)/(dx) = e^x`

Factoring out `(dy)/(dx)` yields:

`(dy)/(dx)(1 + e^(-y)) = e^x => (dy)/(dx) = (e^x)/(1 + e^(-y))`

Replacing ` y - e ^(-y)` for `e^x` yields:

`(dy)/(dx) = (y - e ^(-y))/(1 + e^(-y))`

Hence, evaluating `(dy)/(dx)` , using implicit differentiation, under the given conditions, yields `(dy)/(dx) = (y - e ^(-y))/(1 + e^(-y)).`

We’ve answered 320,038 questions. We can answer yours, too.

Ask a question